A Potential Concomitant Sellar Embryonic Remnant-Associated Collision Tumor: Systematic Review - Wang, Mingdong; Fu, Qianhui; Song, Mingjing; Zhao, Zongmao; Wang, Renzhi; Zhang, John; Ma, Wenbin; Wang, Zhanxiang (Frontiers in Oncology, 2021)
Background The well-known, diagnosis of concomitant Rathke’s cleft cyst (RCC) and other sellar lesion is difficult, because two types of lesions are closely related and represent a continuum from simple RCCs to the more complex lesions. The purpose of this study is to assess incidence in different age groups, to categorize pathohistological subtype, which is incorporated in predictive /prognostic models, and then final, to evaluating of current evidence on collision tumor of the sellar embryonic-remnants tract regarding their biological behavior, pathology. Methods Utilizing a PubMed database. Information about demographic, clinical, and age was summarized and analyzed by using univariable and multivariable models. The author noted it has the same cell type when it is alone and mix, assessed their histologic patterns. Results The incidence rates were similar in three different age groups 40-49-year-old (24.57%), 50-59-year-old groups (19.54%), and older than 60 year age groups (22.98%)). We found various types of sellar lesion that squamous metaplasia（SM）+ goblet cells（GC） (HR 46.326), foamy macrophages（FM） (HR 39.625), epithelial cells and multinucleated giant cells or cholesterin（EM） (HR 13.195), a cavernous portion of the right internal carotid artery（CP-ICA） (HR 9.427), epithelial cells with ciliated cuboidal（EC-CC） (HR 8.456), independently associated with RCC pathological status. These divergent AUC(0.848)for Hypo as RCC, 0.981 for RCC co PA, 0.926 for CD & CP co RCC, and subtype of PA (HR 4.415, HR 2.286), Hypo (HR3.310) , CD & CP (HR2.467), EC&DC&PG&SGR (HR1.068) coexisting with the risk of RCC values of a comorbid lesion may reflect etiologic heterogeneity of co-derivation and the different effects of some risk factors for tumor subtypes. Our analyses suggested that RCC had the greatest collision accuracy for the subtype pituitary adenoma AUC 0.981(95%confidence interval [CI]: 0.959-1.005), and collision aneurysm had the poorest AUC 0.531(95%CI:0.104-0.958). Conclusion This study showed that the histopathological changes of these patients with sellar embryonic-remnants associated collision tumors showed a highly consistent epithelial cell replacement(renew) /or accumulation process, and the RCC cyst wall similar in structure to the tracheobronchial airway epithelium with progenitor cell characteristics. The accuracy of a collision between RCC and other tumors is different